2010
DOI: 10.1111/j.1863-2378.2010.01365.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bacterial Culture and Real‐Time PCR for the Detection ofSalmonellain Grow–Finish Pigs in Western Canada Using a Bayesian Approach

Abstract: Impacts• Using a Bayesian model specifying dependence between tests, RT-PCR sensitivity (Se) and specificity (Sp) were estimated to be 90% (95% probability interval 74, 97) and 99% (98, 99), respectively, while culture Se was 92% (75, 99).• The correlation between RT-PCR and bacterial culture was found to bias estimates of test accuracy; researchers should adjust for this correlation during analysis.• The RT-PCR evaluated in this study performed comparably to culture and may be a useful alternative to culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…If previously designed primer pairs listed in Table 3 are used, several PCR assays would fail to detect numerous Salmonella spp., whose sequences are currently available in GenBank. This could partially explain the false-negative results encountered in Salmonella detection [36]. At the same time, although invA is capable of excluding non- Salmonella strains, our BLAST sequence analysis of invA demonstrated that some non- Salmonella groups such as E. coli, Staphylococcus aureus subsp.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…If previously designed primer pairs listed in Table 3 are used, several PCR assays would fail to detect numerous Salmonella spp., whose sequences are currently available in GenBank. This could partially explain the false-negative results encountered in Salmonella detection [36]. At the same time, although invA is capable of excluding non- Salmonella strains, our BLAST sequence analysis of invA demonstrated that some non- Salmonella groups such as E. coli, Staphylococcus aureus subsp.…”
Section: Discussionmentioning
confidence: 90%
“…In general, the invA- based PCR assays provide higher sensitivity, shorter turnaround time, and reduced labor cost, making it an excellent alternative to conventional culture method for pathogen detection [29]. However, conspicuous variations in sensitivity and specificity of invA- based PCR assays have been documented by numerous studies [1,29-35], and one of the possible reasons for such discordant outcomes may be due to the use of different primers for gene detection in the assays such as conventional or qPCR [36]. In an effort to better understand the variations caused by the usage of different primers for gene detection in PCR assays, we systematically evaluated the most commonly used invA primer pairs for the detection of Salmonella in thirteen (n = 13) PCR assays (Table 3; Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was initially assumed that the Se ISO and the Se PCR were conditionally independent; i.e., the probability of a positive result for culture is the same regardless of the result obtained for the PCR and vice versa. However, since both tests were performed on the same BPW-enriched samples, some degree of Se correlation between tests was not unexpected (40). Hence, a conditional independence model for two tests was initially carried out in two populations (29) using Winbugs software (http://www.mrc-bsu.cam.ac.uk/bugs/).…”
Section: Methodsmentioning
confidence: 99%
“…It is essential to note that qPCR methods detect both viable and nonviable bacteria while culture methods detect only viable bacteria. Such disparity in culture versus qPCR results has also been observed during Salmonella detection/isolation from swine feces (33).…”
Section: Figmentioning
confidence: 92%